Valor pronóstico de la escala FullPIERS para el desarrollo de síndrome de HELLP en gestantes con preeclampsia en el Hospital Regional de Loreto “Felipe Santiago Arriola Iglesias” durante el año 2024 - Aroni Valderrama, Fredy (2025)
The FULLPIERS scale is a model that has been intrinsically validated by a group of experts, with the cooperation of various institutions that dedicated a lot of time and constitutes a tool with statistical validity, capable of stratifying according to maternal risk in real time to pregnant women diagnosed with preeclampsia, and thus being able to distinguish those preeclamptic women with a high risk of evolving to serious and / or disastrous outcomes within a period of 48 hours (counted from hospital admission) and precisely one of these complications is HELLP Syndrome, so that an action can be taken based on the results it shows. The purpose of this study is to determine whether the FULLPIERS scale has prognostic value for the development of HELLP Syndrome in pregnant women with preeclampsia at the Felipe Santiago Arriola Iglesias Regional Hospital of Loreto in 2024. This research work is a prospective cohort study, longitudinal type. The population is made up of 287 pregnant women diagnosed with preeclampsia, who were treated in the different services of the Regional Hospital of Loreto, and the sample is represented by 262 of these pregnant women who meet the inclusion criteria. Our statistical analysis of rates - proportions was carried out using the chi-square test (χ²) and Odds ratio (OR)